The Influence of The STAD Cooperative Learning Model and Interest on Student Learning Outcomes In Geography Subjects - Repriani, Repriani; Kohar, Farida; Murboyono, Rahmat; Arkew, Habtu Worku; Achour, Zyed (Program Magister Teknologi Pendidikan Universitas Jambi, 2022)
The aim of this research is to determine whether there is an influence of STAD cooperative learning and interest on student learning outcomes in geography subjects at Public High School 10 Batanghari. As a result, the STAD cooperative learning model and interest influence student learning outcomes in geography subjects at Public High School 10 Batanghari. Conclusion The results of the hypothesis test are 1) There are differences in learning outcomes for students with high interest in learning and low interest in learning who are taught using the STAD learning model; 2) There are differences in student learning outcomes between high interest in learning and low interest in learning taught using conventional methods; 3) There are differences in learning outcomes between groups of students who have a high interest in learning who are taught using the STAD cooperative learning model when compared with the learning outcomes of groups of students who have a high interest in learning who are taught using conventional methods; 4) There are differences in learning outcomes between groups of students who have low interest in learning who are taught using the low STAD cooperative learning model when compared to groups of students who have low interest in learning who are taught using conventional methods; 5) There is no interaction between the application of the learning model and interest in student learning outcomes. The conclusion of this research is that there is an influence of STAD cooperative learning and interest on student learning outcomes in geography subjects.